Hydrogen capture by porphyrins at the TiO2(110) surface. Issue 44 (26th October 2015) - Lovat, Giacomo; Forrer, Daniel; Abadia, Mikel; Dominguez, Marcos; Casarin, Maurizio; Rogero, Celia; Vittadini, Andrea; Floreano, Luca
Abstract : Porphyrin iminic nitrogen atoms spontaneously capture two additional hydrogen atoms on the TiO2 (110) surface. Abstract : Metal-free porphyrin molecules adsorb on the rutile TiO2 (110) surface with their pyrrolic nitrogen atoms atop the O-bridge rows, whereas the iminic nitrogen atoms capture two additional hydrogen atoms. Hydrogenation occurs spontaneously at room temperature, irrespective of the distance of the polypyrrolic macrocycle from the surface, as varied by changing the porphyrin functionalization.